Pengembangan Budaya Pesantren dalam Mewujudkan Pendidikan Islam Moderat Berbasis Multikultural - Aldina Fauziyah; Mohammad Makinuddin; Hani’atul Khoiroh (YASIN, 2026)
Although moderate Islamic education is often positioned merely as theoretical curriculum content in the classroom, practice in Islamic boarding schools (pesantren) shows that religious moderation is in fact formed through everyday experiences that unfold over a full 24 hours. This study aimed to reveal how pesantren culture is transformed into a multicultural ecosystem that effectively instills the values of moderation in practical terms. The research employed a library study method by reviewing literature related to pesantren, religious moderation, and multicultural education. The findings indicate three main points. First, pesantren build an inclusive ecosystem through the management of student heterogeneity and cultural acculturation processes that enable continuous encounters across diverse social and cultural backgrounds. Second, the internalization of moderation values is carried out through daily traditions such as sorogan and roan, which cultivate discipline, responsibility, and social empathy through consistent habituation. Third, the Filosofi Ikan di Air Asin (Fish in Salty Water Philosophy) serves as an ethical framework that guides students to remain adaptive in a plural society without losing the integrity of their creed. The study concludes that strengthening pesantren culture is an effective preventive strategy to counter radicalism while simultaneously reinforcing social cohesion at the national level through the formation of a moderate habitus within Islamic educational environments.